The Atmosphere and Ionosphere Elementary Processes, Discharges and Plasmoids - Bychkov, Vladimir; Golubkov, Gennady; Nikitin, Anatoly; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The book presents research devoted to atmospheric and ionospheric science reported during the Conference (3z(BAtmosphere, Ionosphere, Safety(3y (Bheld in Kaliningrad, Russia in July 2010. It consists of works devoted to physics of elementary processes, aerosols, ionosphere dynamics, microwave discharges and plasmoids. Such a wide range of topics presents a comprehensive analysis of this atmospheric science including trends and questions which exist to be solved.s
Ionization of Excited Atoms in Thermal Collisions -- Elementary Processes Involving Rydberg Molecules in a Strong Laser Field -- Nanoaerosols in the Atmosphere -- Electromagnetic Drivers in the Upper Atmosphere: Observations and Modeling -- Discharge Processes in a Stratosphere and Mesosphere During a Thunderstorm -- Vortex Plasmoids Created by High Frequency Discharges.
Keywords: Geography; Meteorology; Astrophysics; Physical geography; Earth Sciences; Meteorology/Climatology.; Environmental Physics; Extraterrestrial Physics, Space Sciences; Fluid- and Aerodynamics